Differential effect of the DRD3 genotype on inflammatory cytokine responses during abstinence in amphetamine-dependent women. (November 2018) - Kuo, Shin-Chang; Yeh, Yi-Wei; Chen, Chun-Yen; Huang, Chang-Chih; Ho, Pei-Shen; Liang, Chih-Sung; Lin, Chun-Long; Yeh, Ta-Chuan; Tsou, Chang-Chih; Yang, Bao-Zhu; Lu, Ru-Band; Huang, San-Yuan
Highlights: Chronic use of amphetamine increased both pro- and anti-inflammatory cytokines in female AD patients. The immune imbalance may persist for 4 weeks or more. IL-8 levels maybe a potential early state-marker in recovery from amphetamine-induced neuroinflammation. DRD3 rs6280 TT genotype may be associated with greater recovery in general inflammatory cytokines during abstinence. Abstract: Amphetamine exposure impacts on innate and adaptive immunity and DRD3 may modulate the effect of amphetamine on the immune response. We assessed the immune-cytokine markers in 72 female patients with amphetamine dependence (AD) at baseline and after 4-week drug abstinence and in 51 healthy women. Multiplex magnetic bead assay was used to measure the plasma cytokine expression level simultaneously in all participants and DRD3 rs6280 polymorphism was genotyped in patients. We demonstrated an increase of the T helper 1 (Th1) cytokines (IL-2), Th2 cytokines (IL-4, IL-5, IL-6 and IL-10) and other cytokines (IL-1β) in the entire AD cohort. A similar cytokine pattern, along with a significantly decreased IL-8 and IL-10 levels was observed after 4-week abstinence. Among AD patients with DRD3 rs6280 TT genotype, the cytokine expression profile was consistent with total AD cohort at baseline and revealed a significant down-regulated plasma level of the Th1, Th2, and other cytokines except for IL-6 after 4-week abstinence. In AD group with DRD3 rs6280 C allele carrier, we found IL-2 level was significantly higher than healthy controls at baseline and remained higher, accompanied with a borderline increase in IL-4, IL-6 and IL-1β levels after 4-week abstinence. Our results suggest that chronic use of amphetamine increased both pro- and anti-inflammatory cytokines in AD patients, indicating the immune imbalance that may persist for 4 weeks or more. Besides, DRD3 rs6280 TT genotype may be associated with favorable recovery in general inflammatory cytokines during period of abstinence.